19 MALE PSEUDOHERMAPHRODITISM DUE TO 5-ALPHA-REDUCTASE DEFICIENCY. (1st January 2006) - Nuzhat, A.; Rettig, K.; Estrada, B.
Abstract : Background: Steroid 5-alpha-reductase deficiency (5-ARD) is one of the causes of male pseudohermaphroditism. It is a rare autosomal recessive disorder due to the deficiency of an enzyme responsible for the conversion of testosterone to dihydrotestosterone (DHT). This results in failure of full masculinization of the male genitalia. Case Report: We are reporting a case of a patient who was evaluated in our clinic at the age of 5 months for ambiguous genitalia. Physical exam revealed the presence of scrotalized labia as well as a hypertrophic clitoris and palpable gonads in the labial sacs bilaterally. Serum 17-hydroxy- progesterone level drawn on the second day of life was 266 ng/dL. A serum testosterone level was 159 ng/dL and the karyotype was 46XY. A pelvic ultrasound was done and was interpreted as showing no müllerian duct structures and no ovaries. The repeat serum testosterone and dihydrotestosterone done at Esoterix laboratory at 5 months of age showed levels of 114 ng/dL and 5.2 ng/dL, respectively. The ratio of serum testosterone to dihydrotestosterone was 21.9. A human gonadotrophin stimulation test was done, which increased the levels of serum testosterone to 1, 644 ng/dL and serum dihydrotestosterone to 38 ng/dL. The testosterone to dihydrotestosterone ratio was 43.3, which was highly suggestive of 5-ARD. Gene probe studies were done, which demonstrated no evidence of androgen insensitivity syndrome. Conclusion: 5-ARD should be considered in the differential diagnosis of patients with ambiguous genitalia. Two genes coding for 5-ARD have been identified, each for a slightly different isoenzyme. These genes were studied and identified at our institution. The major issue for 5-ARD is gender assignment at birth; in the US, most infants undergo an early surgical feminizing genitoplasty and are not assigned a gender until after the surgery. Our patient was assigned a gender and after 5 months, once the diagnosis had been established, the gender was changed, which was distressing for the family.